Cover Feature: Electrochemical Oxidation of d‐Glucose in Alkaline Medium: Impact of Oxidation Potential and Chemical Side Reactions on the Selectivity to d‐Gluconic and d‐Glucaric Acid (ChemElectroChem 1/2020). Issue 1 (9th December 2019) - Moggia, Giulia; Kenis, Thomas; Daems, Nick; Breugelmans, Tom
Abstract : The Cover Feature illustrates the valorization of biomass, originated from agricultural, forest and animal residues, obtained through an electrocatalytic process that transforms its derivatives, such as d ‐glucose, into value added chemicals, such as d ‐glucaric acid, which are used to produce bio‐plastics, bio‐fuels, pharmaceuticals, etc. The energy required to sustain this process is generated by a renewable resource, for example, a wind turbine. More information can be found in the Article by G. Moggia et al. on page 86 in Issue 1, 2020 (DOI: 10.1002/celc.201901592 ).